1991
DOI: 10.1093/infdis/163.3.598
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Disease, Drug Susceptibility, and Biochemical Patterns of the Unnamed Third Biovariant Complex of Mycobacterium fortuitum

Abstract: Previous studies of Mycobacterium fortuitum identified isolates that did not fit its two recognized biovariants. Eighty-five clinical isolates of this group, the "third biovariant complex", were evaluated. They represented 16% of 410 isolates of M. fortuitum submitted to a Texas laboratory and 22% of 45 isolates in Queensland, Australia. Most infections (76%) involved skin, soft tissue, or bone and occurred after metal puncture wounds or open fractures. Isolates differed from biovar fortuitum in resistance to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
110
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(117 citation statements)
references
References 18 publications
7
110
0
Order By: Relevance
“…peregrinum type III is a rapidly growing mycobacteria belonging to the M. fortuitum group (3) which also includes M. fortuitum, M. fortuitum third variant (19), M. mucogenicum, and M. senegalense. Although M. peregrinum was first proposed in 1962, only in the last years has been systematicly included (20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…peregrinum type III is a rapidly growing mycobacteria belonging to the M. fortuitum group (3) which also includes M. fortuitum, M. fortuitum third variant (19), M. mucogenicum, and M. senegalense. Although M. peregrinum was first proposed in 1962, only in the last years has been systematicly included (20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…fortuitum-group members cause a variety of human infections . Accurate bacterial identification, rising from a relevant classification, is crucial as antimicrobial resistance is species-dependent (Wallace et al, 1991).…”
mentioning
confidence: 99%
“…various carbohydrates and immunodiffusion patterns of strains that belong to the M. fortuitum complex revealed more than one hundred strains that differed from the above species (Silcox et al, 1981; LCvy-FrCbault et al, 1983; Labidi et al, 1984; Wallace et al, 1991). In one study (Wallace et al, 1991), the isolates that did not correspond to recognized species represented 16-22% of the examined strains and were mostly involved in skin, soft-tissue or bone infections.…”
mentioning
confidence: 99%
“…In one study (Wallace et al, 1991), the isolates that did not correspond to recognized species represented 16-22% of the examined strains and were mostly involved in skin, soft-tissue or bone infections. Furthermore, studies of the 16s rRNA (Kirschner et al, 1992; Springer et al, 1995) showed that some of these strains probably belong to an unidentified species.…”
mentioning
confidence: 99%
See 1 more Smart Citation